ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING LOANS (NPL) DI INDONESIA (Studi Pada Bank Umum Konvensional Yang Terdaftar Di Bank Indonesia Tahun 2011-2014) - Mada, Romo Putra; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2015)
Loan is the main source of income of a Conventional Commercial Bank, thus, Commercial Bank is vulnerable to a Non-Performing Loan. Given the global crisis in 1997, many banks were liquidated because of a high Non-Performing Loan in this sector. Although the bank's management has made efforts to prevent, but Non-Performing Loan still occur. This study aimed to examine the effect of Size, loan to deposit ratio, Capital Adequacy Ratio, Operating cost to Operating revenues ratio and Interest Rate of Loans to the Non-Performing Loan. Samples which is used in this study is the Conventional Commercial Bank registered in Bank of Indonesia for the 2011-2014 period. To obtain a valid study results, the sampling technique used in this research is purposive sampling method . A sample of 27 banks was acquired. Analysis method applied in this research is the normality test, autocorrelation test, Test of multicoloniarity, Heteroskidastity Test, Test of Coefficient of Determination R2, Test of Statistic F, Test of Statistic t, and Multiple Linear Regression Analysis. Based on the results of the partial testing carried out, Operating cost to Operating revenues ratio and Interest Rate of Credit have a positive influence on the Non-Performing Loan. While the loan to deposit ratio, size and Capital Adequacy Ratio have a negative influence on the Non-Performing Loan. Based on the test results of the coefficient of determination R2, variable Size, loan to deposit ratio, Capital Adequacy Ratio, Operating cost to Operating revenues ratio and interest rate of 43.5% loans have effect against non-performing loans. While the rest as much as 56.5% influenced by factors other than variabel of research.